USING ARTIFICIAL INTELLIGENCE FOR FURTHER SUSTAINABLE ENVIRONMENTAL DEVELOPMENT OF THE WORLD - Abdullakhanova Gulbahor; Sayyora Safaeva (Journals Park Publishing, 2025)
Today, the process of development and widespread use of new artificial intelligence technologies is clearly visible, which are becoming a powerful force and can carry, on the one hand, safety and security, and on the other hand, a threat, both for an individual and for of all humanity. This article is devoted to the use of artificial intelligence in the environmental field, which can have a significant role in the success of protecting our planet and its continued existence. Currently, artificial intelligence is capable of helping humanity in many ways, keeping control and analyzing the current situation in the environmental sphere, which is its benefit for professionals and specialists in various fields.
Keywords: Artificial intelligence, ecology, environmental problems, neural network, sustainable development, environment, natural resources, sustainable tourism.